A Systematic Review of Mexican American Elders with Type-2 Diabetes under Family Care of Medication Administration in Borderland - Hsueh-Fen S. Kao; Diana L. Woods; Minzhi Ye; Lin Chen; Maria A. Amaya; Show-Mei Lin (Journal of Aging Research And Healthcare, 2017)
The prevalence of type-2 diabetes (T2DM) among Mexican-American older adults along the U.S.-Mexico border region is at epidemic proportions. Healthcare reform is trending toward long-term home-based management of chronic conditions. Under the Mexican cultural norm of familism, daily care for elders is also often provided by family caregivers whose competence levels may vary. Adherence to the prescribed medication regimen is critical to attainment of optimal glucose control. However, there is a startling lack of literature that addresses the link between family medication administration and care recipients’ health outcome. This paper explores the role of culture in medication administration by family caregivers of elders with T2DM from the perspective of caregiver capabilities and caregiving demands. A critical review of the literature offers suggestions to guide future studies.
Keywords: diabetes